2018
DOI: 10.1111/sed.12494
|View full text |Cite
|
Sign up to set email alerts
|

Basinal setting and origin of thick (1·8 km) mass‐flow dominated Grand Conglomérat diamictites, Kamoa, Democratic Republic of Congo: Resolving climate and tectonic controls during Neoproterozoic glaciations

Abstract: The Kamoa sub‐basin, in the south‐eastern part of the Democratic Republic of Congo, is a rift basin that hosts a world‐class stratiform copper deposit at the base of a very thick (1·8 km) succession of matrix‐supported conglomerates (diamictite) (Grand Conglomérat Formation) that has been interpreted by some as the product of deposition in the aftermath of a planet‐wide glaciation. Newly available subsurface data consisting of more than 300 km of drill core throws new light on the origin of diamictite and asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 137 publications
0
19
0
Order By: Relevance
“…Interpretation.-The discrimination between glaciogenic and nonglaciogenic diamictite can be problematic (e.g., Visser 1994;Eyles and Januszack 2007;Le Heron et al 2017;Vesely et al 2018;Kennedy et al 2019). Most of the clasts found in this FA appear to be locally derived (pink to green granite and gneiss; Figs.…”
Section: Fa3: Matrix-supported Diamictite Subaqueous Mass-flow Depositsmentioning
confidence: 95%
See 2 more Smart Citations
“…Interpretation.-The discrimination between glaciogenic and nonglaciogenic diamictite can be problematic (e.g., Visser 1994;Eyles and Januszack 2007;Le Heron et al 2017;Vesely et al 2018;Kennedy et al 2019). Most of the clasts found in this FA appear to be locally derived (pink to green granite and gneiss; Figs.…”
Section: Fa3: Matrix-supported Diamictite Subaqueous Mass-flow Depositsmentioning
confidence: 95%
“…However, the absence of striations on clasts, combined with their local origin, suggests that the diamictite does not originate from glaciogenic processes. The chaotic aspect of the deposits and the normal grading, rather point toward a scenario whereby successive debris, mass, or hyperconcentrated flows deposited the sediments (e.g., Prior and Bornhold 1988;Mulder and Alexander 2001;Caron et al 2011;Moxness et al 2018;Kennedy et al 2019). Basal shear at the base of the flow is evidenced by rip-up clasts which show virtually no displacement (Fig.…”
Section: Fa3: Matrix-supported Diamictite Subaqueous Mass-flow Depositsmentioning
confidence: 98%
See 1 more Smart Citation
“…Rocks of the Paleo-Mesoproterozoic basement, that are bordering the KCB to the west, are uncomformably overlain by a transgressive basal conglomerate. Formations overlying this conglomerate along the basement are the Mwale (Grand Conglomérat) to the southeast, and Mwashya or undistinguished Roan rocks to the northwest and to the south (François, 1973, 1995Kennedy et al, 2019. Recent observations questioning the autochthonous massif in that region showed that: (1) the Mamfwe anticline, eastern portion of the autochthonous massif ( Fig.…”
Section: Geological Settingmentioning
confidence: 99%
“…Given this, distinguishing between diamictites of glacial versus slope origin in the rock record is a vital, yet often problematic, component of correct palaeo‐environmental and climate interpretations (Kennedy, Eyles, & Broughton, ; Letsch & Kiefer, ). This is especially true for Cryogenian diamictites of Death Valley, which often record coeval glaciation and rifting (Eyles & Januszczak, ; Miller, ; Prave, ; Vandyk et al., ).…”
Section: Introductionmentioning
confidence: 99%